Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1558/lst.v3i1.28803
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing metalinguistic knowledge

Abstract: Framed within a Sociocultural theory perspective to L2 learning, this article investigated the potential of a suite of pedagogical materials for enhancing metalinguistic knowledge in a foreign/second (L2) language context. The linguistic focus of the project was the tense-aspect system, specifically the contrast between the Preterite and the Imperfect in Spanish given the challenges this poses for L2 learners. Six L1 English university students of L2 Spanish at intermediate level volunteered to participate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…As reported in previous sections, there have been several studies dedicated to the teaching and learning of this linguistic notion within a SCT perspective (Gánem--Gutiérrez, 2016;García, 2012García, , 2014Negueruela, 2003;Negueruela & Lantolf, 2006;Polizzi, 2013); however, this is the first proposal that presents a complete pedagogical sequence focused on how to present aspect in the SHL classroom.…”
Section: Hlls and The Acquisition And Development Of Aspect In Spanishmentioning
confidence: 92%
See 1 more Smart Citation
“…As reported in previous sections, there have been several studies dedicated to the teaching and learning of this linguistic notion within a SCT perspective (Gánem--Gutiérrez, 2016;García, 2012García, , 2014Negueruela, 2003;Negueruela & Lantolf, 2006;Polizzi, 2013); however, this is the first proposal that presents a complete pedagogical sequence focused on how to present aspect in the SHL classroom.…”
Section: Hlls and The Acquisition And Development Of Aspect In Spanishmentioning
confidence: 92%
“…In L2 English, studies have examined C--BI for teaching locative prepositions (White, 2012) and sarcasm (Kim, 2013); in L2 Chinese, tense (Lai, 2012) and topicalization (Zhang, 2014); and in German, declensions (Walter & van Compernolle, 2015). In the Spanish L2 classroom, C--BI has been used to explore aspect, tense, and mood (Negueruela, 2003(Negueruela, , 2008; locative prepositions (Serrano--López & Poehner, 2008); the development of literary metaphor (Yáñez--Prieto, 2008); the use of motion events as mediational tools for giving directions (Aguiló--Mora & Negueruela, 2015); the sociopragmatics of self--representation, social distance, and power applied to tú/usted (van Compernolle, Webber, & Gomez--Llaich, 2016); and the concept of aspect applied to the relationship between Spanish preterite and imperfect tenses (Gánem--Gutiérrez 2016;García, 2012García, , 2014Negueruela, 2003;Polizzi, 2013).…”
Section: The Implementation Of Concept--based Instruction In the L2 Cmentioning
confidence: 99%
“…Definition, verbalization, and performance data were triangulated to measure instructional effectiveness, following Negueruela (2003). Definition data (to address RQ1) were collected three times using a series of questions modeled after García (2012) and Gánem–Gutiérrez's (2016) metalinguistic test (see Appendix ). The definition pretest was given after PRET and IMP morphology had been taught but before the 3‐day lesson sequence that contrasted their uses.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional instruction for PRET/IMP is organized around rules of thumb, but the rules have been criticized as constituting an inaccurate and confusing laundry list of disconnected notions (e.g., Frantzen, 1995; Llopis–García et al., 2012; Yáñez Prieto, 2008) that tend to promote the formation of inaccurate explicit knowledge about PRET/IMP (Kissling, 2021). Newer approaches to teaching PRET/IMP that are based on advances in cognitive linguistics (e.g., Castro, 2006; Doiz, 2013; Doiz–Bienzobas, 1995) and sociocultural theory (SCT) (e.g., Gánem–Gutiérrez, 2016; García, 2012; Negueruela, 2003; Negueruela & Lantolf, 2006; Polizzi, 2013; Yáñez Prieto, 2008) have the potential to address the deficiencies of conventional instruction, but they are often so complex as to be inaccessible to learners and instructors who are nonexperts in second language acquisition (SLA; Comajoan Colomé, 2014; Salaberry et al, 2013; Williams et al, 2013). In light of this situation, it is clear that we need an approach to teaching the PRET/IMP contrast that both reflects a sophisticated understanding of the phenomenon and yet, at the same time, can be implemented by a wider range of instructors.…”
mentioning
confidence: 99%
“…Due to the fact that Gal'perin's approach is not prescriptive, early research into CBI for L2 learning explored issues relating to the operationalisation of the model as such with a focus on how to materialise concepts (e.g., Lapkin et al, 2008;Negueruela, 2003Negueruela, , 2008Swain et al, 2009). Furthermore, research into the potential effectiveness of the approach has reported its beneficial impact on L2 learning, although the studies in question tended to be descriptive, primarily documenting development through qualitative case studies (e.g., Gánem-Gutiérrez, 2016;Poehner & Infante, 2017). In some cases, descriptive statistics are reported based on pre-test/post-test designs, but only for a CBI group (e.g., Gánem-Gutiérrez & Harun, 2011;Kuepper & Feryok, 2020;Lantolf & Tsai, 2018).…”
Section: Instructional Conditions and Experimental Treatmentmentioning
confidence: 99%